Automatic Night Patrol System with Raspberry Pi - Gophika, T.; Brindha Judith Yeshvanthi, P.J.; Jivitha, K.R. (2023 International Conference on Sustainable Computing and Smart Systems (ICSCSS), 2023)
Safety issues happen to be one of the major delimiting factors for people to feel free in their journey and life at late nights and darker areas. S tronger laws and effective punishments aren't enough to feel safe. Thus, here a solution is proposed that assists in ensuring advanced security in remote areas where safety is a real concern. Recent developments in security systems use techniques like continuous live relay using IP cameras that transmit video surveillance to a user. These surveillance techniques need continuous human intervention to monitor the transmitted video to check for identifying a triggered situation that is either in live or from the past. S ystems that use techniques like ADT to identify an emergency situation without continuous human monitoring are expensive as it requires multiple sensors and need skilled service personnel to maintain the system and update the software. The proposed 'Automatic Night Patrol System with Raspberry Pi' proposes an alternative solution to the challenges faced with the existing technology. Unlike security systems that need humans for surveillance, this study can detect an emergency situation automatically and capture the images of identified situation and send it to the user for further rescue operation if needed. An alert signal is also sent to notify the user about identified danger situation. This reduces the human intervention as the user is not required to involve much in surveillance operation but rescue operation. This study uses Python language for coding and no complex algorithms are used. This reduces the expense of installing a security system for any individual/organisation unlike a complex security system. This research work also focuses on providing enhanced co-ordination in Night patrol system by making it automatic with IoT. It is a security patrolling robot embedded with cameras and sensors to effectively monitor and detect human motion. The simulation and the output are expected to be more precise to actually realize and transfer the model into realistic idea in launch. Transmission of alert signal is done with the help of MQTT protocol. Raspberry Pi IC is used in the proposed model. MIME standard is used for the e-mailing purpose (transmission of images).